Pengaruh tipe industri, mekanisme corporate governance, dan ukuran perusahaan terhadap corporate social responsibility disclosure - NURAINUN BANGUN; CHRISTIE ANDHIKA; HENRYANTO WIJAYA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2016)
The purpose of this research is to get empirical provement about the influence of profile, corporate governance mechanism (size of boards of directors, proportion of boards of directors independcy, and audit committee), and company size significantly on corporate social responsibility disclosure. This research obtainted data from financial statements of manufacture sector companies. The company researched consisted of 30 companies for each period during 2012-2014. The statistic method that was used to test the hypothesis was the multiple linier regression. The result of this research shows that profile, size of boards of directors, proportion of boards of directors independcy, and audit committee not influence significantly on corporate social responsibility disclosure. While, the effect of company size on corporate social responsibility disclosure is significant